Há cegueira nos pintores? : editorial - Queiroz, João Paulo, 1966- (2018)
The listening and the revisiting of the works that precedes ourselves allows us to add to wealth to the present and to expand the options for other interventions in the future. This is a redemption option, a recognition option: that is the meaning of the 17 articles selected for the 7th issue of Gama journal. Bridges are settled to get to know the route of authors like Villari Herrmann, Edgard da Rocha Miranda, Raymonde Carasco, Arminio Kaiser, António Alfredo, Roberto Rodrigues, among others. This is the goal of Gama journal: to launch the look of artists on the works of other artists in order to resume knowledge